2008
DOI: 10.5254/1.3548213
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Oxidation and Tire Aging - A Review

Abstract: While a new tire may have excellent resistance to crack initiation and propagation between the steel belts, an aged tire of the exact same construction can exhibit dramatically reduced crack growth resistance, which in some cases may contribute to tire failure. This article will review the research that has gone into quantifying the rate of oxidation the steel belt rubber oxidizes in different climates from tire samples retrieved from consumers' vehicles. The information obtained from the field is then compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…However, it was observed that the M100 value for the control SMR L compound decreased after aging at 100°C for 24 hours, whereas the SMR L compounds with the presence of antioxidants increased. The decreasing of M100 after aging for the control compound might be caused by anaerobic degradation, in which the modulus and EB would decrease with degradation . The decrement of the property is related to modifications of the original crosslink structure during the aging process.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was observed that the M100 value for the control SMR L compound decreased after aging at 100°C for 24 hours, whereas the SMR L compounds with the presence of antioxidants increased. The decreasing of M100 after aging for the control compound might be caused by anaerobic degradation, in which the modulus and EB would decrease with degradation . The decrement of the property is related to modifications of the original crosslink structure during the aging process.…”
Section: Resultsmentioning
confidence: 99%
“…Very limited studies have been done to investigate the thermal aging behavior of rubber particles/granulates at a relatively high temperature. [8][9][10] Considering the application scenarios of rubber granules in the bitumen modification process, both aerobic and anaerobic aging of rubber may occur. When rubber particles are immersed in the hot bitumen, mainly anaerobic aging of rubber takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Although aging of rubber is a natural phenomenon which is ultimately unavoidable, the prevention and retardation of aging, and proactive life prediction of rubber have been active research topics for many years. [8][9][10][11][12][13][14][15][16] Owing to its plastic nature, there are inherently flaws in the molecular structure of rubber, making it easily susceptible to aging due to invasion of external oxygen atoms. SBR's macromolecular chain has a type of unsaturated double bond structure, which readily reacts with oxygen atoms under common ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Rubber is apt to suffer from aging due to high temperature, illumination, oxidation, hydrolysis, biodegradation, salt spray, and other environmental factors, which degrades its quality and characteristic over time, and shortens its useful lifetime. Although aging of rubber is a natural phenomenon which is ultimately unavoidable, the prevention and retardation of aging, and proactive life prediction of rubber have been active research topics for many years . Owing to its plastic nature, there are inherently flaws in the molecular structure of rubber, making it easily susceptible to aging due to invasion of external oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%